Analisis Tingkat Literasi Keuangan, Perencanaan Dan Pengelolaan Keuangan Pribadi: Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Teuku Umar - Fira Safira; Linda Rahmazaniati; Cut Sri Firman Hastuti; Rimal Mahdani; Rina Maulina (AKUNTANSI 45, 2025)
Industry 4.0 allows generation Z to more easily obtain information which is an important part of achieving financial goals in the modern era. Good personal financial management is another important aspect of individual welfare, several factors that can support the effectiveness of personal financial management are financial literacy and financial planning. This study aims to analyze and see how much the level of financial literacy, planning and personal financial management of students of the Faculty of Economics, Teuku Umar University. Data were collected through structured interviews with 12 students of the Faculty of Economics, Teuku Umar University with differences in age, gender, batch and study program. The results of this study indicate that students of the Faculty of Economics, Teuku Umar University already have an understanding of financial literacy, and apply it in their daily lives such as having a strong saving habit both at the bank and independently, and starting to plan long-term investments. Students are also increasingly aware of the importance of financial planning and are able to distinguish between needs and wants. Positive financial management behavior can also be seen from the habit of making budgets, not rushing when making financial decisions and preparing emergency funds. This study provides recommendations and solutions for students of the Faculty of Economics, Teuku Umar University in improving financial management.